1975
DOI: 10.5254/1.3545039
|View full text |Cite
|
Sign up to set email alerts
|

Scrap Tire Disposal Process

Abstract: Experimental results are presented which indicate that scrap rubber vulcanizates, typical of today's tires, can be depolymerized to a product which is essentially a carbon black dispersion in oil. The depolymerization is free radical in nature and requires an efficient chain transfer agent to prevent hardening of the vulcanizate and to increase the rate of depolymerization. The product, termed “Depolymerized Scrap Rubber” (DSR), should be useful, particularly as a rubber compounding ingredient and as a fuel oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Tire char can be used as a reinforcing filler for low-value rubber goods and perhaps as a printing ink pigment after appropriate treatment (Petrich, 1991). Several studies have been conducted on using tire char, instead of carbon black, for filling polymers and vulcanizates (Crane and Kay, 1975; Kawakami et al, 1980;Makarov and Drozdovski, 1991). The quality of vulcanizates filled with tire char tends to lie between the qualities of vulcanizates produced with high-activity and low-activity commercial carbon blacks.…”
Section: ;mentioning
confidence: 99%
See 1 more Smart Citation
“…Tire char can be used as a reinforcing filler for low-value rubber goods and perhaps as a printing ink pigment after appropriate treatment (Petrich, 1991). Several studies have been conducted on using tire char, instead of carbon black, for filling polymers and vulcanizates (Crane and Kay, 1975; Kawakami et al, 1980;Makarov and Drozdovski, 1991). The quality of vulcanizates filled with tire char tends to lie between the qualities of vulcanizates produced with high-activity and low-activity commercial carbon blacks.…”
Section: ;mentioning
confidence: 99%
“…However, rubber reclaim generated from scrap tires does not have suitable properties for use in tire manufacture and must be used for low-value rubber goods (Makarov and Drozdovski, 1991). Moreover, production with rubber reclaim can be more costly than production with virgin raw materials (Crane and Kay, 1975). As a result, the majority of scrap tires accumulate in dumps, posing hazards such as disease and accidental fires.…”
Section: Introductionmentioning
confidence: 99%
“…Crane and Kay (11) have reported that scrap rubber vulcanizates could be depolymerized to a product known as "Depolymerized Scrap Rubber" (DSR), which should be useful, particularly as a rubber compounding ingredient and as a fuel-oil extender.…”
Section: Introductionmentioning
confidence: 99%
“…Several workers have explored these possibilities. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Kim and Burford studied the utilization of waste tires in polar and nonpolar rubbers. [15] When WTR is used with a polar matrix such as chloroprene rubber, the compatibility has to be taken into account.…”
Section: Introductionmentioning
confidence: 99%